Insights into the utility of small form air quality monitoring in health care environments: lessons learned from the University Hospitals Birmingham NHS Foundation Trust - Cowell, Nicole; Baldo, Clarissa; Williams, Kawun; Muller, Catherine; Hou, Siqi; Rooney, Daniel; Zhong, Jian; Healey, Scarlett; Bloss, William James; Bartington, Suzanne E. (Frontiers in Public Health, 2025)
Air pollution is a major environmental and public health challenge, with exposure to air pollution linked to 29,000–43,000 premature deaths annually in the UK. The National Health Service (NHS) experiences increased burden on its services due to air pollution related disease. Acute NHS Trusts and other healthcare settings are often locations with high inpatient and outpatient populations at enhanced vulnerability to air pollution related disease, including the young and older adults, and those with chronic health conditions. Many UK healthcare facilities are located in areas of poor air quality. Non-communicable disease from air pollution (PM2.5 and NO2) could cost health and social care providers estimated to >£18billion in the UK (between 2018 and 2035) if pollutant concentrations are not reduced. The NHS Long Term Plan recognised the need for NHS services to take action to mitigate air pollutant emissions, including those arising from site activities and patient, visitor and staff travel. However undertaking air quality monitoring and implementing targeted air-pollution interventions can present organisational, financial, and logistical challenges. Furthermore, evidence of the effectiveness of highly localised interventions is limited in the healthcare context. The recent expansion in utility of small form air quality sensors offers major potential to overcome some of the challenges in monitoring and understanding efficacy of targeted interventions at healthcare settings. Here, we present a case study from Queen Elizabeth Hospital Birmingham, a tertiary site managed by University Hospitals Birmingham NHS Foundation Trust. This study assesses the feasibility of small form monitoring (diffusion tubes and sensors) for evaluating local air quality interventions in healthcare settings, via an assessment of a localised traffic management scheme aiming to reduce local air pollutant concentrations.